KEEFEKTIFAN PEMBELAJARAN MATEMATIKA BERBASIS KONTRUKTIVISME PADA MATA KULIAH MATEMATIKA DASAR - Aryo Andri Nugroho (Universitas Jenderal Soedirman, 2012)
This research aims to improve mathematics learning achievement of first semester student majoring biology at IKIP PGRI Semarang using mathematics learning based on constructivism in basic mathematics courses. This type of study is a research of Quasy Experimental. The population is the first semester of students majoring in biology education IKIP PGRI Semarang which consists of five classes. By random sampling technique we choose two classes, class 1A as a class experiment and class 1E as a control class. Variables in this research are the process skills (X) as the independent variable and learning achievement (Y) as the dependent variable. Data collection had been done by observation and learning achievement tests and for analyzing by comparison and influence tests. The results showed that completeness test has average 70.20 . It means that completeness had been and there is a achievement difference between the experimental class and control class. Beside that, we find that variable of process skill has a positive effect to the learning achievement by regression equation and the effect is 20.3%. It is shown that learning at experiment class is effective.